1982
DOI: 10.1002/1097-0142(19820301)49:5<1043::aid-cncr2820490533>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative surveillance of colorectal carcinoma

Abstract: Two-hundred-forty patients with previously resected colorectal carcinoma were investigated for neoplasia of six months, 12 months and then at yearly intervals during a four-year period. Physical examination, occult blood, rigid sigmoidoscopy, barium enema and colonoscopy were used during the surveillance. Out of 304 colonoscopies, 68 were positive for neoplasia, 11 metachronous, and 17 recurrent cancers with 66 tubular adenomas and nine villous adenomas were found. Barium enema detected 38% of the lesions. Occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Three other studies have evaluated the role of colonos¬ copy after colorectal cancer resection.4? 13 Unger and Wanebo7 evaluated the usefulness and yield of colonoscopy on 56 patients selected from their tumor registry who had undergone curative resection at some time during the previous five years (mean interval after resection, 34 months). Their positive findings consisted of 12 polyps (three larger than 1 cm) and one asymptomatic suture line recurrence in nine patients, despite normal barium enema films.…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies have evaluated the role of colonos¬ copy after colorectal cancer resection.4? 13 Unger and Wanebo7 evaluated the usefulness and yield of colonoscopy on 56 patients selected from their tumor registry who had undergone curative resection at some time during the previous five years (mean interval after resection, 34 months). Their positive findings consisted of 12 polyps (three larger than 1 cm) and one asymptomatic suture line recurrence in nine patients, despite normal barium enema films.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] Although the updated society guidelines 7-10 include recommendations on the surveillance intervals after CRC surgery, the proportion of a second primary CRCdfurther referred to as metachronous CRC (mCRC)ddid not decrease over the past decade, ranging from 1% to 4% of all patients with CRC. [11][12][13][14][15][16][17][18][19] In the early 80s, Tornqvist et al 11 found that mCRCs account for 2.1% of all CRCs, in a cohort of curatively treated patients with CRC. Two decades later, Green et al 12 found 42 mCRC cases over 15,000 person-years of follow-up, corresponding to a proportion of 1.3%.…”
mentioning
confidence: 99%
“…Incidence of metachronous CRC varies between 0.5%-9%, with an average of 1.6% [2]. Most metachronous tumours were observed within 24 months after polypectomy or CRC surgery.…”
Section: Discussionmentioning
confidence: 99%